2020
DOI: 10.1155/2020/7409853
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin Exacerbates Cellular Injury in Conditionally Reprogrammed Patient-Derived Lung Adenocarcinoma Cells by Aggravating Mitochondrial Impairment and Endoplasmic Reticulum Stress through EphB4/CDC42/N-WASP Signaling

Abstract: Lung cancer is the most common and lethal malignant disease for which the development of efficacious chemotherapeutic agents remains an urgent need. Pristimerin (PRIS), a natural bioactive component isolated from various plant species in the Celastraceae and Hippocrateaceae families, has been reported to exhibit outstanding antitumor effects in several types of cells. However, the underlying mechanisms involved remain poorly understood. Here, we reported the novel finding that PRIS significantly suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…In the mitochondrial pathway, cytochrome-c, Apaf-1, and other apoptotic factors are released into cytoplasm due to the elevated mitochondrial permeability (58,59), which is preceded caspase activation and cell apoptosis (53). The translocation of cytochrome-c from mitochondria into cytoplasm has been observed under pristimerin administration in CRLC (19), CML (43), breast cancer (49), HCC (51), glioma (52), prostate cancer (55), cervical cancer (56), and pancreatic cancer (60). Wu et al have shown that pristimerin can induce cytochrome-c release through a direct action on mitochondria (49).…”
Section: The Intrinsic (Mitochondrial) Pathwaymentioning
confidence: 99%
See 4 more Smart Citations
“…In the mitochondrial pathway, cytochrome-c, Apaf-1, and other apoptotic factors are released into cytoplasm due to the elevated mitochondrial permeability (58,59), which is preceded caspase activation and cell apoptosis (53). The translocation of cytochrome-c from mitochondria into cytoplasm has been observed under pristimerin administration in CRLC (19), CML (43), breast cancer (49), HCC (51), glioma (52), prostate cancer (55), cervical cancer (56), and pancreatic cancer (60). Wu et al have shown that pristimerin can induce cytochrome-c release through a direct action on mitochondria (49).…”
Section: The Intrinsic (Mitochondrial) Pathwaymentioning
confidence: 99%
“…In CRLCs, pristimerin upregulated the levels of Bax, whereas downregulated the levels of Bcl-2 and BIRC6. As a result, cytochrome-c was released from mitochondria accompanied by the attenuation of MMP, eventually intensifying the pristimerin-induced mitochondrial apoptotic pathway (19). Zhang et al have revealed that in treatment with pristimerin, the decline of XIAP and survivin rather than Bcl-2 and Bcl-xL can be observed in UM cells (30).…”
Section: The Intrinsic (Mitochondrial) Pathwaymentioning
confidence: 99%
See 3 more Smart Citations